The Challenges of Living with Inflammatory Bowel Disease: Summary of a Summit on Patient and Healthcare Provider Perspectives - Judith Bray; Aida Fernandes; Geoffrey C. Nguyen; Anthony R. Otley; Joan Heatherington; Jennifer Stretton; Natasha Bollegala; Eric I. Benchimol (Canadian Journal of Gastroenterology and Hepatology)
Canada has one of the highest rates of inflammatory bowel disease (IBD) and the disease represents a significant health, social, and economic burden. There is currently no cure for IBD, although earlier diagnosis and new therapies have improved the overall health outcomes and quality of life for patients. Crohn’s and Colitis Canada is Canada’s only national, volunteer-based charity dedicated to finding cures for IBD and improving the lives of those affected, through research, education, patient programs, advocacy, and increased awareness. On April 30, 2015, Crohn’s and Colitis Canada hosted the “Patient and Healthcare Professional Summit on the Burden of Disease in IBD” to obtain a deeper understanding of the unmet needs of IBD patients and their caregivers. Through personal vignettes, patients articulated a pressing need to increase understanding of the challenges faced by people suffering from IBD among both health care professionals and the general public, develop best practices for navigating life transitions and addressing the unique challenges faced by children with IBD, and provide equitable access to appropriate, effective, and affordable treatments. The recommendations that emerged from the summit will inform about efforts to increase public awareness, inform about advocacy strategies, and contribute to the development of research priorities.